PROMOTING QUALITY OF LIFE AND SUSTAINABILITY. - Paraguassu, Eber Coelho; Cardenas, Anneli Mercedes Celis de (Periódicos Brasil. Pesquisa Científica, 2023)
The promotion of quality of life and sustainability is an interdisciplinary theme of great contemporary relevance. It focuses on finding approaches that balance human well- being with preserving natural resources and the health of the planet. This theme covers a variety of areas, from public health and urban development to environmental conservation and economic policy. The objective of this study is to investigate strategies and practices that seek to improve people’s quality of life in a sustainable way. This study is a bibliographic review, in which a multidisciplinary approach was adopted that integrated qualitative and quantitative analyses. Data collection covered the investigation of specialized literature, relevant case studies and an in-depth analysis of socio-environmental indicators. The results demonstrated that the promotion of quality of life and sustainability requires an integrated approach. Successful initiatives include the implementation of efficient public transport policies, the creation of urban green spaces, the adoption of renewable energies and education for environmental awareness. Public awareness and cross-sectoral collaboration also emerged as critical factors in achieving positive outcomes. Promoting quality of life and sustainability is not just a necessity, but an imperative to ensure a livable future for future generations. The integrated approach, combined with the participation of society and government engagement, can result in an effective balance between human well-being and preservation of the environment. By prioritizing sustainability in all spheres of life, we can aspire to a future where prosperity and care for the planet go hand in hand.